Philippine medical thesaurus on anatomy musculoskeletal system in Bicolano - De los Santos, Maricar S. (2004)
The Multilingual Philippine Medical thesaurus is part of a collaborative effort of the Institute of Library and Information Science, University of the Philippines Diliman, and the College of Medicine, University of the Philippines, Manila. Its main purpose is to come up with a tool for enhanced medical informatics research in the Philippines to aid the Filipino users and therefore lessen the difficulty and misconceptions in medical terminologies employed in the Philippines.